Beyond good & evil children, media and violent times - Picker, Miguel; Sun, Chyng F.; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 2003)
This video examines how the'good and evil' rhetoric, in both the entertainment and the news media, has helped children to dehumanize the enemies, justify their killing and treat the suffering of innocent civilians as necessary sacrifice
Title from title screen
Filmed, edited & graphics, Miguel Picker
Poen narration: Eren Ileri
Keywords: Mass media and children; Mass media and public opinion -- United States; Good and evil